The pro-differentiating capability of a flavonoid-rich extract of Citrus bergamia juice prompts autophagic death in THP-1 cells - Laura Musumeci; Caterina Russo; Udo Schumacher; Giovanni Enrico Lombardo; Alessandro Maugeri; Michele Navarra (Scientific Reports, 2024)
Abstract Acute myeloid leukemia (AML) is a hematologic neoplasm, characterized by a blockage of differentiation and an unconstrained proliferation of immature myeloid cells. Recently, the survival of leukemia patients has increased thanks to the use of differentiating agents, though these may cause serious side effects. Hence, the search for safer differentiating compounds is necessary. Our aim was to assess the pro-differentiating effects of a flavonoid-rich extract of bergamot juice (BJe) in human monocytic leukemia THP-1 cells, an in vitro AML model. For the first time, we showed that treatment with BJe induced differentiation of THP-1 cells, changes in cell morphology and increased expression of differentiation-associated surface antigens CD68, CD11b and CD14. Moreover, BJe enhanced protein levels of autophagy-associated markers, such as Beclin-1 and LC3, as well as induced the phosphorylation of the MAPKs JNK, ERK and p38, hence suggesting a potential mechanism underlying its antiproliferative effects. Indeed, parallel experiments highlighted that BJe was able to hamper THP-1 cell growth. In conclusion, our study suggests that BJe induces the differentiation of THP-1 cells and reduces their proliferation, highlighting its potential in differentiation therapy of AML.